ADAPTASI KABA GADIH BASANAI KE FILM GADIH BASANAI - Desmawardi Desmawardi; Hanefi Hanefi; Maisaratun Najmi (LP2MP3M, INSTITUT SENI INDONESIA SURAKARTA, 2019)
ABSTRACT This paper contains an explanation of the process and results of the adaptation of GadihBasanaikaba to the film scenario of GadihBasanai. Adaptation is a median transfer of a story originating from Kaba, a Tutoring Art media to Audio Visual media (film. This adaptation process refers to Susan Hayward’s thoughts and is sup-ported by Linda Seger thinking. Susan Hayward divides the adaptation process into 6 stages. Linda Seger emphasizes that the good adaptation process uses a thinking base Take Me As I Am.The process and results of this study show that narrative kaba as oral literature is different from narrative scenario (film) . There must be any innovation in order to become narrative film with an obvious causality, motivation, and action.The research also shows thatGadihBasanaikaba experiencing differences or changes in accordance to the expe-rience of life and the era of the speakers. The results of this study are expected to become material for thinking about the development of Bakaba tradition and the development of Indonesian films.